Biblical Quotations in Egidius de Zamora’s Ars Musica: Sources and Purpose of Use (Minerva, 2017)
Johannes Egidius de Zamora, is the author of Ars Musica, the first Hispanic musical treatise of the Middle Ages. Numerous biblical and theological quotations are noticeable in his work. Therefore the paper shall focus on the analysis of the former ones. An outline of Egidius de Zamora’s biography and his Ars Musica precedes the study of biblical quotations. All this provides a clear typology and an understanding about their use within textual, intertextual and musicological issues.
Keywords: biblical reception; Egidus de Zamora; Ars Musica